Probiotic Edamame Yoghurt: A Study on Sensory, Microbiological, and Physicochemical Properties of Fermentation Using Mixed Cultures - Nita Maria Rosiana; Nidzo Mudin Arrifani (JURNAL INFO KESEHATAN, 2025)
One of the primary risk factors for cardiovascular diseases (CVDs) that caused deaths is hypercholesterolemia, which can be identified by high levels of total cholesterol, low-density lipoprotein (LDL), and very low-density lipoprotein (VLDL). Dietary interventions, involving the consumption of soy protein, have been indicated to be effective in reducing LDL cholesterol levels. Edamame, a kind of soybean, is a potential source of soy protein that could be processed into functional foods. The aim of the research was to evaluate the chemical and sensory properties of edamame yoghurt fermented with lactic acid bacteria and probiotic bacteria, potentially contributing to a cholesterol-lowering benefit. The research methodology was a two-factor Randomized Block Design (RBD). The edamame yoghurt was made by combining edamame juice, skim milk powder, and sugar, followed by heat (80-85 °C for 15 minutes), and cooling to 45 °C. The mixture was then inoculated with a combination of lactic acid bacteria (Lactobacillus bulgaricus and Streptococcus thermophilus) and probiotic bacteria (Bifidobacterium bifidum and Lactobacillus acidophilus). Fermentation proceeded at 37 °C for 7 hours.  The pH, total titratable acidity, lactic acid bacteria count, and soluble protein content were analysed. Sensory properties were evaluated using preference and hedonic tests. The results exhibited that the combination of bacterial cultures significantly affected (p<0.05) pH, total soluble protein, and sensory properties of the yoghurt. Bifidobacterium bifidum led to higher acidity pH (3.73-3.78), while Lactobacillus acidophilus resulted in the lowest titratable acidity (0.55-0.63%). The combination of Lactobacillus bulgaricus and Streptococcus thermophilus improved flavor, texture, and fermentation efficiency. The yoghurt’s texture was smooth due to proteolytic activity by lactic acid bacteria. Edamame yoghurt's green color fades during fermentation, and its aroma is less favoured according to panelists, but its creamy texture and mildly acidic taste make it appealing overall.  Edamame yoghurt, a source of soy protein fermented with lactic acid and probiotic bacteria, shows potential for cholesterol reduction.